A Numerical Study of Ground Improvement Technique Using Group of Soil-Column on Peat - Muntohar, A. S., Rahman, M. E, Hashim, R., Islam, M. S (Universitas Putra Malaysia, 2013)
The importance of numerical analysis in investigation of piled embankment over soft soil has been developed since 1990. Several investigators have extended the numerical analysis to model ground improvement using soil-column to support embankment or structures. This paper presents a numerical analysis of the Pulverized Fuel Ash (PFA) column-treated peat and compared with field static-loading test results. Back analysis was performed to determine the material parameters and soil stiffness surrounding soil & soil-column. Two geometrical models were used in this analysis: (a) block (Model A), and (b) column group (Model B). This situation was analyzed using commercially available finite element package PLAXIS 2D ver. 8.2. It is found that both models are reliable to simulate the field static-loading test for column-treated peat. Model B shows a higher stability to failure if compared to Model A.